Locating appropriate areas of municipal waste landfill using TOPSIS method (Case study: Langroud County) - Ali Moghimi Kandlousy; Amin Mohebbi Tafreshi; Ghazaleh Mohebbi Tafreshi (Mashhad University of Medical Sciences, 2018)
ABSTRACT   Background & objective: The lack of suitable landfill for storage and disposal of solid wastes in different parts of Guilan has been not only led to deforestation and agricultural lands destruction, but also jeopardized public health. The Langroud County as a tourist destination of Guilan province is also affected by solid wastes. Therefore, the present study aims to locate the new appropriate area for municipal sanitary landfill, taking into account environmental standards in Langroud County.   Materials & Methods: In this research, 20 criteria were used in accordance with the standards of the Iranian Environmental Protection Agency, the Alberta State Environmental Authority of Canada, the Minnesota Pollution Control Agency and the British Columbia Environmental Ministry as criteria for locating. TOPSIS method was used in combining the criteria maps in ArcGIS software environment.   Results: After passing TOPSIS and combining the layers obtained in the ArcGIS software environment, the final map of urban landfill location within the study area was classified into five classes (very weak, weak, moderate, good and excellent).   Conclusion: Based on the results, five prestigious areas in the south and southwest of the city with the highest degree of fit and excellent grade were proposed as new areas of urban solid waste disposal for the city of Langroud.